Analysis of Business Development Services in Improving Taxpayer Compliance of Micro, Small and Medium Enterprises - Rudi Andrean; Milla Sepliana Setyowati (Universitas Teuku Umar, 2022)
This study aims to analyze the role of implementing business development services (BDS) to improve the tax compliance of MSME taxpayers. To do this, a qualitative approach with the Library Research method is used. Data is collected by reviewing journals, conference publications, books, and other sources related to the research problem, such as news from credible sources, as well as final project research from another relevant research. The results of the study show that Business Development Services (BDS) is a form of business development services that facilitates MSME actors to grow. In Indonesia, the Director General of Taxes uses this program to encourage tax compliance by integrating it with tax socialization. This program then provides various event platforms that increase tax knowledge and perceptions of tax justice. The implication for the Tax Office is to be able to develop a BDS program that is as attractive as possible for MSMEs. This study provides originality as the first qualitative study to investigate the effect of BDS on tax compliance.